A cladistic analysis and classification of the subfamily Bembicinae (Hymenoptera: Crabronidae), with a key to the genera - Nemkov, Pavel G.; Lelej, Arkady S. (Zootaxa, 2013)
A cladistic analysis of the digger wasp subfamily Bembicinae based on morphological characters is presented. The under-lying data matrix comprises 83 terminal taxa (coded on genus-level) and 64 morphological characters. The resulting strict consensus tree was used as the basis for a revised tribal and subtribal classification of the Bembicinae. Based on a previ-ously published classification, we herewith propose a change: the tribe Heliocausini Handlirsch 1925, stat. resurr. (com-posed of Acanthocausus Fritz & Toro 1977, Heliocausus Kohl 1892, and Tiguipa Fritz & Toro 1976) is separated from Bembicini Latreille 1802. Four tribes are recognized within the subfamily Bembicinae and seven subtribes within the tribe Gorytini and two subtribes in the tribe Nyssonini, based on the present cladistic analysis.The subtribe Nurseina Nemkov & Lelej, subtrib. nov. (comprising of Nippononysson Yasumatsu & Maidl 1936 and Nursea Cameron 1902) is separated from other genera in the tribe Nyssonini Latreille 1804. An new identification key to the genera of the Bembicinae is pro-vided.